Landscape Population Genomics of Forsythia (Forsythia suspensa) Reveal That Ecological Habitats Determine the Adaptive Evolution of Species - Yang, Jie; Miao, Cai-Yun; Mao, Run-Li; Li, Yong (Frontiers in Plant Science, 2017)
Understanding the genetic mechanisms of adaptation to environmental variables is a key concern in molecular ecology and evolutionary biology. Determining the adaptive evolutionary direction and evaluating the adaptation status of species can improve our understanding of these mechanisms. In this study, we sampled 20 populations of Forsythia suspensa to infer the relationship between environmental variables and adaptive genetic variations. Population structure analysis revealed that four genetic groups of F. suspensa exist resulting from divergent selection driven by seven environmental variables. A total of twenty-six outlier loci were identified by both BayeScan and FDIST2, twenty-three of which were environment-associated loci (EAL). Environmental association analysis revealed that the environmental variables related to the ecological habitats of F. suspensa are associated with high numbers of EAL. Results of EAL characterization in F. suspensa are consistent with the hypothesis that ecological habitats determine the adaptive evolution of this species. Moreover, a model of species adaptation to environmental variables was proposed in this study. The adaptation model was used to further evaluate the adaptation status of F. suspensa to environmental variables. This study will be useful to help us in understanding the adaptive evolution of species in regions lacking strong selection pressure.